Analysis of Linear Antibody Epitopes on Factor H and CFHR1 Using Sera of Patients with Autoimmune Atypical Hemolytic Uremic Syndrome - Trojnár, Eszter; Józsi, Mihály; Uray, Katalin; Csuka, Dorottya; Szilágyi, Ágnes; Milosevic, Danko; Stojanović, Vesna D.; Spasojević, Brankica; Rusai, Krisztina; Müller, Thomas; Arbeiter, Klaus; Kelen, Kata; et al. (Frontiers in Immunology, 2017)
Introduction: In autoimmune atypical hemolytic uremic syndrome (aHUS) the complement regulator factor H (FH) is blocked by anti-FH autoantibodies, while 90% of the patients carry a homozygous deletion of its homologue protein, CFHR1. The functional consequence of FH-blockade is widely established; however, the molecular basis of autoantibody binding and the role of CFHR1 deficiency in disease pathogenesis are still unknown. We performed epitope mapping of FH to provide structural insight in the autoantibody recruitment on FH and potentially CFHR1. Methods: Eight anti-FH positive aHUS patients were enrolled in this study. With overlapping synthetic FH and CFHR1 peptides we located the amino acids (aa) involved in binding of acute and convalescence stage autoantibodies. We confirmed the location of the mapped epitopes using recombinant FH domains 19-20 that carried single-aa substitutions at the suspected antibody binding sites in three of our patients. Location of the linear epitopes and the introduced point mutations was visualized using crystal structures of the corresponding domains of FH and CFHR1. Results: We identified three linear epitopes on FH (aa1157-1171; aa1177-1191; aa1207-1226) and one on CFHR1 (aa276-290) that are recognized both in the acute and convalescence stages of aHUS. We observed a similar extent of autoantibody binding to the aHUS specific epitope aa1177-1191 on FH and aa276-290 on CFHR1, despite 7 of our patients being deficient for CFHR1. Epitope mapping with the domain constructs validated the location of the linear epitopes on FH with a distinct autoantibody binding motif within aa1183-1198 in line with published observations. Summary: According to the results, the linear epitopes we identified are located close to each other on the crystal structure of FH domains 19-20. This tertiary configuration contains the amino acids reported to be involved in C3b and sialic acid binding on the regulator, which may explain the functional deficiency of FH in the presence of autoantibodies. The data we provide identifies the exact structures involved in autoantibody recruitment on FH and confirms the presence of an autoantibody binding epitope on CFHR1.